CRISPR‑Cas9 engineered Saccharomyces cerevisiae for endolysin delivery to combat Listeria monocytogenes - Sáez Moreno, David; Cunha, Joana; Melo, Luís Daniel Rodrigues; Tanaka, Kenya; Bamba, Takahiro; Hasunuma, Tomosiha; Azeredo, Joana; Domingues, Lucília (Applied microbiology and biotechnology, 2025)
Listeriosis is an infection caused by the consumption of food contaminated with Listeria monocytogenes. It leads to febrile gastroenteritis, central nervous system infections, and even death in risk populations. Bacteriophage endolysins selectively kill bacteria hydrolyzing their cell walls and have emerged as a potential tool for listeriosis control. Ply511 is an anti-Listeria endolysin that has activity against all serovars of L. monocytogenes. The yeast Saccharomyces cerevisiae has been used to produce endolysins for biocontrol, but prior efforts relied on plasmids, which can lead to gene loss and include selection markers unsuitable for therapeutic use. Integration of endolysins in its genome has also been previously demonstrated, relying however, on selection markers for selection and maintenance of the modifications. This study explores S. cerevisiae as a generally regarded as safe (GRAS) platform for producing and displaying Ply511 through CRISPR-Cas9 integration, offering a marker-free and stable solution for Listeria biocontrol. Our results demonstrate that the surface display of Ply511 does not lead to bacterial reduction. In contrast, we show that yeast secreting endolysin significantly reduces L. monocytogenes in cells, supernatants, and cell extracts. The strongest effect was observed with concentrated spent supernatant and cell extract, which reduced L. monocytogenes below the lower limit of quantification. Additionally, the spent supernatant exhibited active anti-Listeria activity in milk. This study highlights yeast-secreted endolysins as a promising platform for listeriosis control and demonstrates the yeast secretion of endolysins can be used for the biocontrol of pathogenic bacteria. Open access funding provided by FCT|FCCN (b-on). This study was supported by the Portuguese Foundation for Science and Technology (FCT) under the scope of the strategic funding of UIDB/04469/2020 and UIDP/04469/2020 unit and a Ph.D. grant UI/ BD/151411/2021 to D.S.M. This work was also supported by Kobe University Strategic International Collaborative Research Grant (Type B Fostering Joint Research).